1983
DOI: 10.2307/1422811
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Positive Effect in Adults and Attention to Portion of Stimulus Array

Abstract: In three experiments, adult humans were tested in a feature-positive or feature-negative simultaneous symbol task. In Experiment 1, some persons focused on the correct side of the stimulus cards, whereas other persons focused on the not-correct side of the stimulus cards. The feature-positive group learned faster than the feature-negative group did in the correct side condition; the feature-negative group learned faster than the feature-positive group did in the not-correct side condition. In Experiments 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The difficulty of FN learning is consistent with the FP effect demonstrated in other discrimination designs, which show that discrimination is more rapidly acquired when the feature signals reinforcement than when it signals nonreinforcement (Jenkins and Sainsbury, 1969;Reberg and LeClerc, 1977;Hearst, 1978;Brown et al, 1983;Lotz et al, 2012;Abramson et al, 2013). Interestingly, the difference between FP and FN learning appears to be greater in the CTA/DDL model than the difference demonstrated in discrimination procedures using a reward contingency (e.g.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The difficulty of FN learning is consistent with the FP effect demonstrated in other discrimination designs, which show that discrimination is more rapidly acquired when the feature signals reinforcement than when it signals nonreinforcement (Jenkins and Sainsbury, 1969;Reberg and LeClerc, 1977;Hearst, 1978;Brown et al, 1983;Lotz et al, 2012;Abramson et al, 2013). Interestingly, the difference between FP and FN learning appears to be greater in the CTA/DDL model than the difference demonstrated in discrimination procedures using a reward contingency (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Although FP and FN discrimination procedures in general appear operationally symmetrical, early research has suggested various asymmetries between the acquisition of FP and FN discriminations (Jenkins and Sainsbury, 1970; Hearst, 1984). For example, FP discriminations are typically acquired faster than FN discrimination in experiments using the traditional light/tone procedures and the discriminated goal-tracking designs (Jenkins and Sainsbury, 1969; Reberg and LeClerc, 1977; Hearst, 1978; Brown et al ., 1983; Lotz et al ., 2012; Abramson et al ., 2013; Andrade et al ., 2021). Furthermore, FP and FN discriminations have been shown to have different neurobiological mediation (Holland et al ., 1999; Sakimoto and Sakata, 2014; Ito and Lee, 2016) and drugs trained as a positive vs. negative feature acquire different properties (e.g.…”
Section: Introductionmentioning
confidence: 99%